2014
DOI: 10.1177/2050313x14561778
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine augmentation with agomelatine in a patient with obsessive-compulsive disorder and suicidal behaviors

Abstract: Obsessive-compulsive disorder is a chronic and disabling condition that often proves to be treatment resistant. Of the patients suffering from obsessive-compulsive disorder, 10%–27% may attempt suicide at least once in their life. We report the case of a patient who presented severe obsessive-compulsive disorder symptoms and attempted suicide ingesting 25 tablets of fluoxetine (20 mg). The patient was treated with venlafaxine and agomelatine and showed improvement of obsessive symptoms and suicidal ideation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…23 Another patient with OCD, who was treated with 300 mg of venlafaxine and 25 mg of agomelatine, also showed improvement of symptoms and fewer episodes of suicidal ideation. 24…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Another patient with OCD, who was treated with 300 mg of venlafaxine and 25 mg of agomelatine, also showed improvement of symptoms and fewer episodes of suicidal ideation. 24…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a reduction in escitalopram to 20 mg daily was also possible. 22 In a male patient, the addition of agomelatine 25 mg/day to escitalopram 10 mg/day resulted in a remarkable Two 27,28 Two 23,24 N/A One 26…”
Section: Successful Combinations Of Agomelatine With Other Antidepres...mentioning
confidence: 99%
See 1 more Smart Citation
“…108 When added to classical pharmacological agents used for OCD (eg, escitalopram, venlafaxine, clomipramine, risperidone, and/or aripiprazole), agomelatine has been found to improve OC symptoms in several cases of treatment-resistant OCD. [109][110][111] In some cases, this led to full remission after ∼3 months of treatment, 109 and in reports with longitudinal monitoring, clinical improvements were often sustained over several months. 110,111 A multiple case study reported considerable clinical improvements in three out of six cases of treatment-resistant OCD.…”
Section: Melatonin Agentsmentioning
confidence: 99%
“…[109][110][111] In some cases, this led to full remission after ∼3 months of treatment, 109 and in reports with longitudinal monitoring, clinical improvements were often sustained over several months. 110,111 A multiple case study reported considerable clinical improvements in three out of six cases of treatment-resistant OCD. 112 Interestingly, two of the three individuals who responded to agomelatine initially presented with sleep disruptions.…”
Section: Melatonin Agentsmentioning
confidence: 99%